Transactions Of Adia Lab: Interdisciplinary Advances In Data And Computational Science - Simon, Horst (Annual Adia Lab Transactions In Data Science And Finance, 2025)
Transactions of ADIA Lab is a peer-reviewed publication that captures the pioneering research emerging from ADIA Lab's interdisciplinary efforts in computational and data science. This inaugural volume reflects the Lab's rapid evolution into a global research hub, showcasing significant contributions in computational finance, the digital economy, advanced computational methods, and trustworthy AI. The collection highlights groundbreaking advancements, including geometric approaches to asset allocation, AI-driven financial modeling, quantum-safe encryption, and ethical frameworks for AI. By bridging theory and practice, the publication underscores ADIA Lab's commitment to developing innovative, real-world solutions that address some of today's most pressing challenges in finance, technology, and beyond.With a strong emphasis on collaboration, Transactions of ADIA Lab brings together leading researchers, industry experts, and policymakers to explore the transformative potential of computational science. This volume not only presents state-of-the-art methodologies but also demonstrates ADIA Lab's dedication to fostering global partnerships, as seen in its collaborations with institutions in Spain and beyond. By integrating advanced computational techniques with practical applications, the research featured here paves the way for more secure financial systems, resilient digital infrastructures, and ethical AI frameworks. As ADIA Lab continues to grow, this publication serves as a testament to its vision of harnessing technology to drive meaningful and lasting impact across industries and society.